Distribución espacio-temporal de la radiación solar neta en superficie sobre el trópico americano del Hemisferio Norte - Campos, Edwin F. (1996)
The results of Pinker and Laszlo's physical model for solar radiation budget are used in order to analize the daily net surface solar radiation (Q*) on tropical regions of the Northern lkmisphere of the Americas. The values of Q* arc averaged for grid points spaced 2.5°, between longitudes 55°O and 120°0 and latitudes 0° and 35°N, for each of the 12 months of the year, from March 1985 to December 1988. The results show significative differences in the values of Q* between the land and oceanic areas, due possibly to different albedos and climatic factors. On the Caribbean Sea and the Gulf of Mexico. it is observed a great relationship of Q* with the position of the sun through the year, which shows a weak influence of the synoptic scale meteorological systems upon the short wave radiation in this region. A persistence of minimum values of Q* is found over the Eastern-equatorial Pacific and Northwestern Sud America, which it is associated to the cloudiness originated by the Inter-tropical Convergence Zone (ITCZ) and to the "anchoring low" to the south of Panama and to the west of Colombia.